Optimalisasi Motivasi Menghafal Al-Qur'an melalui Strategi Dakwah di Akun Instagram @ruangnderes - Dovianti Ainurohmah; Rifqi Ishar Yasser; Alfi Maulani; Anas Azhimi Qalban (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In the digital era and advances in social media, research on how to utilize the Instagram platform to increase motivation in memorizing the Al-Qur'an is still limited. The research was conducted with the aim of investigating the da'wah strategies used by the Instagram account @ruangnderes and how these strategies help increase individual motivation in memorizing the Al-Qur'an. Using a qualitative approach with content analysis, this research observed posts, captions and follower interactions. The research results show that @ruangnderes succeeded in increasing motivation by selecting relevant content, conveying messages creatively, and actively interacting with his followers. This strategy makes a positive contribution to the individual's enthusiasm and desire to achieve the goal of memorizing the Qur'an in the current digital era. Thus, this research contributes indirectly to providing valuable insights into how social media can be utilized effectively in religious contexts. Utilizing social media such as Instagram as a da'wah platform has opened up new opportunities in spreading religious messages and motivating individuals to study the teachings of the Koran more deeply. The success of the @ruangnderes account in increasing motivation to memorize the Qur'an through social media shows the great potential that digital technology has in supporting the development of spirituality and religious activities.